C9orf72-Related Neurodegenerative Diseases: From Clinical Diagnosis to Therapeutic Strategies - Zampatti, Stefania; Peconi, Cristina; Campopiano, Rosa; Gambardella, Stefano; Caltagirone, Carlo; Giardina, Emiliano (Frontiers in Aging Neuroscience, 2022)
Hexanucleotyde expansion in C9orf72 has been related to several phenotypes to date, complicating the clinical recognition of these neurodegenerative disorders. An early diagnosis can improve the treatment of patients, promoting the early administration of therapeutic supportive strategies. Here, we report known clinical presentations of C9orf72-related neurodegenerative disorders, pointing out suggestive phenotypes that can benefit of a genetic characterization of patients. According to the great clinical variability, clinical and instrumental evaluation and supportive therapeutical approaches are described for frequent and rare manifestations of disease. Furthermore, to improve the understanding of molecular pathways of disease and potential therapeutical targets, a detailed description of cellular mechanisms related to pathological effect of C9orf72 is reported. New promising therapeutical strategies and ongoing studies are reported highlighting their molecular role in the cellular pathological pathways of C9orf72. These therapeutical approaches acting at a molecular level are particularly promising because they can stop the disease before the development of neuronal damage. The knowledge of clinical and molecular features of C9orf72-related neurodegenerative disorders improves the therapeutical application of known strategies and will lay the basis for the development of new potential therapies.